METHODOLOGICAL MODEL OF TEACHING CLINICAL DISCIPLINES TO FUTURE SPECIALISTS USING DIGITAL TECHNOLOGIES - A. K. Jamolov; S. Yu. Ashurova (Sciental Journals Publishing, 2025)
This article presents a methodological model for teaching clinical disciplines in medical colleges of Uzbekistan through integration of three evidence-based pedagogical methods enhanced by digital technologies. The model centers on collaborative consultation learning, case conference methodology, and clinical debate as active learning approaches that develop clinical reasoning, critical thinking, and evidence-based practice competencies. Drawing on constructivist learning theory, experiential pedagogy, and situated learning frameworks, the model positions digital technologies—including simulation platforms, virtual patients, telemedicine systems, and AI-assisted tools—as enablers rather than drivers of educational transformation. Within Uzbekistan's context of comprehensive healthcare reforms (2018-2024) and expanding digital infrastructure, this model addresses challenges of mid-level medical education quality, workforce preparation, and evidence-based practice integration. Evidence from systematic reviews and implementation studies demonstrates significant improvements in clinical reasoning (effect sizes 0.64-1.93), critical thinking development (doubled utterances in debate interventions), and interprofessional collaboration (79-90% improvement rates). The article provides practical implementation guidance including five-phase roadmap, faculty development strategies, and contextual adaptations for medical colleges navigating pedagogical modernization.
Keywords: Medical education, clinical teaching methods, digital technologies, collaborative learning, case conferences, clinical debate, Uzbekistan, pedagogical methodology, mid-level healthcare education